A Comparative Clinical Study to Determine the Efficacy of Bhudhatrayadi Yoga and Metformin in the Management of Madhumeha w.s.r. to Type II Diabetes Mellitus (AYUSHDHARA, 2023)
Prameha is a chronic disease that is described in all the classics of Ayurveda. Madhumeha is categorised as a subtype of Vataja Prameha. Vata Dosha is mainly vitiated in Madhumeha. The patient passes large quantity of urine which is Kashaya (astringent), Madhura (sweet), Pandu (pale) and Ruksha (dry). Madhumeha is the final stage of all the Prameha when left untreated for long time becomes difficult to treat. In modern medicine signs and symptoms of Madhumeha resembles Type II Diabetes Mellitus. Diabetes is a metabolic disease and is characterised by increase in blood glucose levels, deficiency of insulin or resistance to insulin uptake. 40 patients were selected from the IPD and OPD of Kayachikitsa Department of R.G.G.P.G. Ayurvedic College and Hospital, Paprola, Himachal Pradesh. 20 patients were managed with Bhudhatrayadi Yoga and 20 patients were managed with Tablet Metformin. Bhudhatrayadi Yoga showed moderate improvement in subjective parameters of Madhumeha in the study.